Review of active control of circular cylinder flow. (15th August 2022) - Chen, Wen-Li; Huang, Yewei; Chen, Changlong; Yu, Haiyang; Gao, Donglai
Abstract: Fluid flow around a circular cylinder is ubiquitous in nature and in various industrial applications. The periodic von Kármán vortex shedding from the cylinder is one of the primary factors contributing to flow-induced vibrations of structural components in the ocean, coastal, and bridge engineering. Because flow-induced vibrations cause structural damage, it is essential to develop effective ways to suppress alternating vortex shedding and manipulate circular cylinder flow. Therefore, active control schemes for mitigating flow-induced vibrations have garnered attention from various researchers in recent decades. In contrast to passive control schemes, active control schemes have the advantages of controllability and maneuverability. This selective literature review provides a retrospect and discusses the recent progress in several active control schemes for circular cylinder flow, including suction/blowing, synthetic jets, electromagnetic forcing, rotation, forced oscillation, thermal effects, acoustic excitation, moving surfaces, and feedback control strategies. In addition, some perspectives on AI-based active control are proposed and discussed briefly. Highlights: This selective literature review gives a retrospect and recent progress in classical active control schemes for circular cylinder flow. Some perspectives of artificial intelligence-based active control are also proposed and discussed briefly.